Hepatocyte and keratinocyte growth factors and their receptors in human lung emphysema - Bonay, Marcel (BioMed Central, 2005)
BACKGROUND: Hepatocyte and keratinocyte growth factors are key growth factors in the process of alveolar repair. We hypothesized that excessive alveolar destruction observed in lung emphysema involves impaired expression of hepatocyte and keratinocyte growth factors or their respective receptors, c-met and keratinocyte growth factor receptor. The aim of our study was to compare the expression of hepatocyte and keratinocyte growth factors and their receptors in lung samples from 3 groups of patients: emphysema; smokers without emphysema and non-smokers without emphysema. METHODS: Hepatocyte and keratinocyte growth factor proteins were analysed by immunoassay and western blot; mRNA expression was measured by real time quantitative polymerase chain reaction. RESULTS: Hepatocyte and keratinocyte growth factors, c-met and keratinocyte growth factor receptor mRNA levels were similar in emphysema and non-emphysema patients. Hepatocyte growth factor mRNA correlated negatively with FEV1 and the FEV1/FVC ratio both in emphysema patients and in smokers with or without emphysema. Hepatocyte and keratinocyte growth factor protein concentrations were similar in all patients' groups. CONCLUSION: The expression of hepatocyte and keratinocyte growth factors and their receptors is preserved in patients with lung emphysema as compared to patients without emphysema. Hepatocyte growth factor mRNA correlates with the severity of airflow obstruction in smokers.